Masyarakat Baduy dan pengobatan tradisional berbasis tanaman - Permana, R. Cecep Eka (UI Scholars Hub, 2009)
A Baduy community in general is still bound by the traditional rules (pikukuh). One of the pikukuh said lojor teu meunang dipotong, pendek teu meunang disambung, which means